Metastatic Breast Carcinoma to The Uterine Cervix - An Unusual Presentation - Varghese, Maymol P; Raju, Sreeja; MC, Savithri; Augustine, Joy; Varghese, Mathew (Annals of Pathology and Laboratory Medicine, 2021)
Uterine cervix involvement as a site of metastasis from a distant primary tumor is rare. Metastasis from breast carcinoma in a patient undergoing treatment is even rarer. The present case report is of a 47-year-old lady with history of carcinoma breast on treatment and who was referred to our hospital with complaints of lower limb oedema, low backache and postmenopausal whitish discharge per vaginum. Per vaginal examination revealed a lesion arising in the cervix extending up to the anterior vaginal wall suggestive of a clinical diagnosis of carcinoma cervix. Subsequent biopsy from the lesion showed malignant cells arranged in Indian file pattern and focal alveolar pattern, hinting at a diagnosis of Invasive lobular carcinoma metastasis. The neoplasm was positive for ER, PR and GATA-3 and negative for Her2/neu and E-cadherin confirming our diagnosis. Although rare, the poor outcome in such patients makes it even more important for its identification and the need for them to undergo careful routine gynecologic examination.